RETRACTED: Students' attitudes towards learning in the context of digitalization: Resources and risks - Shcherbakova Tatyana; Misirov Dinamutdin; Akopyan Marina; Shostak Yegor; Gshiyants Roman; Urdabaeva Lazat (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001